(untitled) (Journal of Economic Research & Business Administration, 2015)
The article analyses the sources of income as an economic factor that make up the family income and the impact of social programs to reduce poverty in Kazakhstan. Also, given the information and information about how to determine trends in the types of sources of income for 2001-2010, the policy is evaluated States on social protection of the population.